Mathematical game theory and applications - Mazalov, Vladimir (West Sessex : Wiley, 2014)
Mathematical Game Theory and Applications combines both the theoretical and mathematical foundations of game theory with a series of complex applications along with topics presented in a logical progression to achieve a unified presentation of research results. This book covers topics such as two-person games in strategic form, zero-sum games, N-person non-cooperative games in strategic form, two-person games in extensive form, parlor and sport games, bargaining theory, best-choice games, co-operative games and dynamic games. Several classical models used in economics are presented which include Cournot, Bertrand, Hotelling and Stackelberg as well as coverage of modern branches of game theory such as negotiation models, potential games, parlor games and best choice games.
References 405-410p.; Index 411-414p.
Keywords: Cooperative games; Network games; Optimal stopping games; Negotiation models